Embodying Musical Heritage in a New–Old Profession: American Jewish Cantorial Schools, 1904–1939. Issue 1 (16th January 2017) - COHEN, JUDAH M.
Abstract: Current scholarship on music in Jewish life generally views American cantorial training as a postwar process of transplantation, translating a culture decimated by the Holocaust into a higher education program in the United States. Recently available digital repositories of historical materials, however, show at least five organized efforts to establish American cantorial schools between 1904 and 1939. I closely examine these efforts here, which reveal during this period a complicated and active negotiation surrounding the role of the cantor—and music more generally—in American Jewish life. Organizers of these schools engaged in active dialogue with cantorial colleagues in central and eastern Europe, subsequently creating institutional training models that imbued the cantor with a character, history, musical repertoire, and professional lifecycle compatible with the United States' religious marketplace. Understanding the urge to establish these schools in the first half of the twentieth century, and the tendency to forget or minimize these efforts after World War II, offers insight into the flexibility of musical tradition as it sought to reassert itself on American soil.